Effect of carbon dioxide gas on the indian meal moth, Plodia Interpunctella (HUB.) (Lepidoptera: Phycitidae) - Gharib, M.S.A.; El-Fishawi, A.A.; Aamir, M.M.I.; Shalaby, A.A.; El-Bana, D.T.M. (2008)
Different developmental stages of the Indian meal moth, Plodia interpunctella were exposed to a modified atmosphere of carbon dioxide in air-tight containers for different exposure periods. Also, some biological aspects of stages obtained from eggs and larvae that survived from CO2 treatments were studied. Cumulative mortality percentages of the different stages were increased as the exposure period to the tested gas (COb2(B) increased. Complete mortality was recorded after 8, 8, 8 and 2 days for eggs, larvae, pupae and adults, respectively. Adult stage was the most sensitive to the gas than the other stages. High levels of larval mortality occurred among those descended from the gas- survived eggs especially of three days old. Percentage of larval mortality of obtained from gas-treated eggs increased as the exposure period to gas increased. Percentage of larval pupation clearly decreased for larvae obtained from gas- exposed eggs for the longest period. First larvae were more sensitive to the gas than the older ones especially in the shortest period of exposure. However, survived young larvae recorded the highest percentage of pupation than the third and fifth instars. Emergence of adults descended from eggs and larvae that survived from CO2 treatments clearly obtained as the exposure period to the gas increased.s
Includes reference.
Summary in Arabic.
1
Keywords: Indianmeal moth; Indianmeal moth -- Control; Carbon dioxide -- Research